1984
DOI: 10.1139/v84-324
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of rhodamine 6G on montmorillonite and laponite, elucidated from electronic absorption and emission spectra

Abstract: The adsorption of the cationic dye rhodamine 6G by montmorillonite (Wyoming bentonite) and laponite (synthetic hectorite) was studied by visible and fluorescent spectroscopy and by X-ray diffraction methods. Adsorption of the dye takes place by the mechanism of cation exchange. X-ray data indicate that the adsorbed cationic dye is located in the interlayer spaces of both minerals. It was found that adsorption prevents the dimerization of the dye, and gives rise to red shifts of the principal absorption band of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 13 publications
3
67
0
1
Order By: Relevance
“…This metachromasy is attributed to the aggregation of the dye after it is adsorbed on the clay surface. Grauer et al (1984) have proposed that the adsorption of R6G on Laponite and montmorillonite prevents the dimerization of the dye. This difference might be due to the different conditions used in the separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This metachromasy is attributed to the aggregation of the dye after it is adsorbed on the clay surface. Grauer et al (1984) have proposed that the adsorption of R6G on Laponite and montmorillonite prevents the dimerization of the dye. This difference might be due to the different conditions used in the separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…The R6G dimer adsorbed at the internal surface, with an intermonomeric distance shorter than the externally adsorbed dimer, is a more constrained aggregate, owing to the limitation of the interlamellar space. Grauer et al (1984) assumed the possibility of dye aggregation in the inter-particle space of flocculated samples. In the present study, however, flocculated samples are not considered because of the sample conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have focused on the adsorption of cationic organic dyes to negatively charged smectites (Chu and Johnson, 1979;De et al, 1974;Ghosal and Mukherjee, 1972;Grauer et al, 1984;Pham Thi Hang and Brindley, 1970;Narine and Guy, 1981;Venugopal and Nair, 1974), Margulies et al (1985 suggested a method of photostabilization of pesticides which is based on coadsorbing on a clay surface the photolabile pesticide and an adequate organic cation that acts as energy acceptor. In such a system the organic cation must be strongly attached to the surface of the clay in order to prevent contamination of soil and water.…”
Section: Introductionmentioning
confidence: 99%
“…In excess AO, the clay is gradually peptized. At this stage the dispersed clay platelets form small tactoids with monomeric AO in the interlayer space and at the same time adsorb dimerie and polymeric AO cationic species at the solidliquid interface.The adsorption of metachromic dyes by the trioctahedral smectite-like phase 'Laponite' and the effects of adsorption on the electronic absorption and emission spectra of the clay-dye suspension have been studied by several investigators (Avnir et al, 1986; Cenens & Schoonheydt, 1988;Cenens et al, 1990;Endo et al, 1986Endo et al, , 1988Grauer et al, 1984; Viaene et al, 1987; Tapia Estevez et al, 1994).It was shown in previous publications that the mechanism of the Laponite flocculation in the presence of aromatic organic cations can be studied from the visible spectra of clay suspensions to which metachromic dyes were added (Yariv et al, 1990). The following spectroscopic features were applied for the study of the colloid behaviour of Laponite during the adsorption of acridine orange [AO, I 3,6 -bis (dimethylamine) acridine hydrochloride] (Garfinkel-Shweky & Yariv, 1995).…”
mentioning
confidence: 99%
“…The adsorption of metachromic dyes by the trioctahedral smectite-like phase 'Laponite' and the effects of adsorption on the electronic absorption and emission spectra of the clay-dye suspension have been studied by several investigators (Avnir et al, 1986; Cenens & Schoonheydt, 1988;Cenens et al, 1990;Endo et al, 1986Endo et al, , 1988Grauer et al, 1984; Viaene et al, 1987; Tapia Estevez et al, 1994).…”
mentioning
confidence: 99%